A further evaluation of the effects of listener training on derived categorization and speaker behavior in children with autism. (November 2015) - Lee, Greg P.; Miguel, Caio F.; Darcey, Emily K.; Jennings, Adrienne M.
Abstract: Previous research has shown that children with autism may accurately categorize visual stimuli after learning to both tact (i.e., speaker behavior) and receptively discriminate (i.e., listener behavior) them using common category names. The purpose of the current study was to further evaluate the effects of category listener training alone on the development of Visual Categorization and Category Tacts with four children diagnosed with autism. We administered standardized language assessments to evaluate participants' skills prior to beginning the study and used a non-concurrent multiple-baseline design across participants. Two of the participants whose language assessments identified both speaker and listener scores greater than 36 months, passed Visual Categorization and Category Tact testing with previously unfamiliar stimuli following Category Listener training. The two participants whose language assessments identified a deficit in either speaker or listener scores failed Visual Categorization and Category Tact testing following Category Listener training. These results suggest that both speaker and listener behavior may be required for the emergence of untrained categorization and tacting following listener training.